2012
DOI: 10.1016/j.dcn.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of decision-making on sensitivity to reward: An fMRI study

Abstract: Studies comparing neural correlates of reward processing across development yield inconsistent findings. This challenges theories characterizing adolescents as globally hypo- or hypersensitive to rewards. Developmental differences in reward sensitivity may fluctuate based on reward magnitude, and on whether rewards require decision-making. We examined whether these factors modulate developmental differences in neural response during reward anticipation and/or receipt in 26 adolescents (14.05±2.37yrs) and 26 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Extending this line of research to include experimental manipulation of preadolescents’ sensitivity to loss and inhibitory control through training or clinical support would provide stronger grounds for causal inference in future research (see for example, the work by Berkman et al, 2012). Additional research on these questions would also undoubtedly benefit from expansion of measurement approaches to include functional neuroimaging as well as behavioral assessment of IGT and EF performance among samples facing higher as well as lower socioeconomic risk (see work by Jarcho et al, 2012). Both approaches have the strong potential to make significant contributions not only to basic science but also to clinical intervention, offering mental health practitioners and educators new tools with which to support healthy outcomes for low-income children as they step across the threshold of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Extending this line of research to include experimental manipulation of preadolescents’ sensitivity to loss and inhibitory control through training or clinical support would provide stronger grounds for causal inference in future research (see for example, the work by Berkman et al, 2012). Additional research on these questions would also undoubtedly benefit from expansion of measurement approaches to include functional neuroimaging as well as behavioral assessment of IGT and EF performance among samples facing higher as well as lower socioeconomic risk (see work by Jarcho et al, 2012). Both approaches have the strong potential to make significant contributions not only to basic science but also to clinical intervention, offering mental health practitioners and educators new tools with which to support healthy outcomes for low-income children as they step across the threshold of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…That is, by including both a passive condition (e.g., passive reward task), which is devoid of agency, and an active condition (e.g., decision-making), which includes agency, the two conditions may be contrasted with one another to isolate the role of agency in reward processing. This approach was taken by Jarcho and colleagues (2012). This study found that neural activity differed by age when the reward-receipt was prescribed by the task (no-choice condition), but was not influenced by age when decision-making was required (choice condition).…”
Section: Basic Principles Underlying Task Design Of Reward Paradigmentioning
confidence: 97%
“…2b) [91, 98, 99]. One study showing that the development of the AIC, alongside that of the striatum, is relevant to even basic reward processing was conducted by Van Leijenhorst et al [91].…”
Section: Activation Of the Aic In Association With Reward Processingmentioning
confidence: 99%